Peminatan Mahasiswa Pembelajaran Kewirausahaan dengan Metode Kelas dan Metode Langsung - Doni Wirshandono Yogivaria; Dimas Emha Amir Fikri Anas (Syntax Idea)
Entrepreneurship is one of the important competencies that need to be owned by students, especially students in the field of economics and business. Entrepreneurship can help students to develop creativity, innovation, and entrepreneurial skills. There are two commonly used entrepreneurship learning methods, namely classroom method and hands-on method. The purpose of this study is to understand students' interest in entrepreneurship learning with class method and direct method. This research uses a qualitative method with a phenomenological approach. The population of this research is students who take entrepreneurship courses in universities in Indonesia. The sample of this research is 10 students who were selected by purposive sampling. The data collection technique used in this research is in-depth interviews. The data analysis technique used in this research is thematic analysis. The results showed that students' interest in entrepreneurship learning with the direct method is higher than the class method. This is due to several factors, namely direct methods provide a more real learning experience for students, direct methods are more interactive and fun for students and direct methods are more in accordance with the learning style of students who are more action-oriented.